2011
DOI: 10.1299/jbse.6.248
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific Finite Element Analyses Detect Significant Mechanical Therapeutic Effects on Osteoporotic Vertebrae During a Three-Year Treatment

Abstract: Analyses of the bone mass alone of osteoporotic vertebrae are not sufficient to predict fracture risks and assess the recovery of bone strength during drug treatment. Instead, finite element analyses (FEAs) is superior, because changes in the vertebral strength are strongly dependent on the inner vertebral stress distribution, which is related to the individual bone shape and bone density distribution in cancellous and cortical region. To investigate how FEAs can detect drug effects, we performed patient-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Imai et al ( 32 ) compared the results of FEM analysis and an actual compression experiment using samples of the thoracolumbar junction collected from fresh cadavers and demonstrated that bone strength and fracture sites can be predicted by FEM analysis. Tawara et al ( 33 35 ) reported the usefulness of FEM analysis for examining osteoporotic spines using CT images of bisphosphonate-treated patients, although they only analyzed limited intervertebral spaces and did not take into account the anatomical variability across the whole spine.…”
Section: Discussionmentioning
confidence: 99%
“…Imai et al ( 32 ) compared the results of FEM analysis and an actual compression experiment using samples of the thoracolumbar junction collected from fresh cadavers and demonstrated that bone strength and fracture sites can be predicted by FEM analysis. Tawara et al ( 33 35 ) reported the usefulness of FEM analysis for examining osteoporotic spines using CT images of bisphosphonate-treated patients, although they only analyzed limited intervertebral spaces and did not take into account the anatomical variability across the whole spine.…”
Section: Discussionmentioning
confidence: 99%
“…However, interest does not subside because of good usage potential in biomedicine [12][13][14][15]. Patient-based medicine became more widespread with the growth of technical abilities in computational mechanics and computed tomography scan quality [16][17][18]. Nowadays, it is possible to not only perform simulation of surgical treatment [19][20][21] but design the endoprosthesis [14,16] and predict biomechanical reaction [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Patient-based medicine became more widespread with the growth of technical abilities in computational mechanics and computed tomography scan quality [16][17][18]. Nowadays, it is possible to not only perform simulation of surgical treatment [19][20][21] but design the endoprosthesis [14,16] and predict biomechanical reaction [22][23][24]. Joint usage of the patient CT-data, patient-based design of the endoprosthesis, and additive manufacturing can increase the quality of the orthopedic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…FEM has then been used to perform stress analyses to quantify strengths under external force from different directions and of different sizes [8]- [10]. Recent attempts that take individual patients' bone strengths into consideration have used CT data to understand the pathology of and assess therapeutic effects in osteoporosis [11] [12]. These techniques have also been used to evaluate surgeries using instrumentation [13].…”
Section: Discussionmentioning
confidence: 99%